Elevated Intracranial Pressure Associated With Exogenous Hormonal Therapy Used for Gender Affirmation. Issue 2 (June 2021) - Nguyen, Huy V.; Gilbert, Aubrey L.; Fortin, Elizabeth; Vodopivec, Ivana; Torun, Nurhan; Chwalisz, Bart K.; Cestari, Dean M.; Rizzo, Joseph F.
Abstract : Background: Addison disease, corticosteroid withdrawal, and taking synthetic growth hormone have been linked with development of intracranial hypertension, but there is still debate on whether administration of other exogenous hormones plays a role in precipitating elevated pressure. The growing use of hormonal therapy for gender affirmation provides an opportunity to explore this possibility. Methods: All transgender patients taking exogenous hormones for female-to-male (FTM) and male-to-female (MTF) transitions who were diagnosed with intracranial hypertension at Massachusetts Eye and Ear Infirmary, Massachusetts General Hospital and Beth Israel Deaconess Medical Center between August 2014 and November 2018 were included in a retrospective review. Visual acuity, type, and dose of exogenous hormone, visual field testing, clinical exam, results of neuroimaging and lumbar puncture, and treatment modalities were catalogued and analyzed. Results: Six transgender individuals were identified. Five were FTM, with an average hormone treatment time of 18.4 months, and one was MTF who had been treated with hormones for 4 years. The average age of all patients was 23.5 years. The average time between onset of symptoms and presentation was 5 months. Fifty percent of the patients reported pulse-synchronous tinnitus, 83% reported positional headache, 33% reported transient visual obscurations, and 16% reported diplopia. Lumbar punctures performed on 4 of the patients revealed elevated opening pressures and normal cerebrospinal fluid constituents. MRI findings consistent with elevated intracranial pressure (ICP) were present in the other 2 patients in whom lumbar puncture was unsuccessful. Four patients were treated with acetazolamide and one was treated with topiramate, with an average follow-up time of 15.7 months. All patients demonstrated bilateral optic disc swelling, and all maintained normal acuity and color vision. Performance on visual field testing was not significantly affected in any patient. Conclusions: This is the largest reported series to date of gender-transitioning patients with intracranial hypertension, including one novel MTF conversion. These observations warrant further investigation into the possible link of exogenous hormonal therapy and elevated ICP and any mechanisms or confounders underlying this potential association.